{0,5+[0,(7)-0,(3)] * 4,5} *4 =
Răspunsuri la întrebare
Răspuns de
2
{0,5+[0,(7)-0,(3)] * 4,5} *4 =
[0.5+(7/9-3/9)*4.5]*4=
[5/10+4/9*45/10]*4=
(5/10+180/90)*4=
(5/10+2)*4=
(0.5+2)*4=
2.5*4=10
[0.5+(7/9-3/9)*4.5]*4=
[5/10+4/9*45/10]*4=
(5/10+180/90)*4=
(5/10+2)*4=
(0.5+2)*4=
2.5*4=10
geoingeras9:
Multumesc mult !!!!!!
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
10 ani în urmă
Ed. tehnologică,
10 ani în urmă